The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1002/hrdq.20055
|View full text |Cite
|
Sign up to set email alerts
|

The influence of perceived characteristics of management development programs on employee outcomes

Abstract: Employees' perceptions of Management Development (MD) programs is the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 62 publications
1
9
0
Order By: Relevance
“…Notwithstanding these differing perspectives on dimensionality, a common view of commitment scholars is that an "affective orientation" lies at the core of individuals' organizational commitment, especially insomuch as it best reflects the attitudinal nature of the construct (Solinger et al, 2008). To this point, numerous studies have used an affective orientation as the sole indicator of organizational commitment (e.g., Kuvaas, 2006;Sturges, Conway, Guest, & Liefooghe, 2005), including many that have specifically explored the effects of HRD factors on employees' organizational commitment (e.g., Ardts, van der Velde, & Maurer, 2010;Bulut & Culha, 2010). We follow in this vein for the present study, particularly as we adopt Mowday and colleagues' (1979) definition of organizational commitment, which has been explicitly identified as having an affective orientation (Meyer & Allen, 1997;Paul & Anantharaman, 2003).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Notwithstanding these differing perspectives on dimensionality, a common view of commitment scholars is that an "affective orientation" lies at the core of individuals' organizational commitment, especially insomuch as it best reflects the attitudinal nature of the construct (Solinger et al, 2008). To this point, numerous studies have used an affective orientation as the sole indicator of organizational commitment (e.g., Kuvaas, 2006;Sturges, Conway, Guest, & Liefooghe, 2005), including many that have specifically explored the effects of HRD factors on employees' organizational commitment (e.g., Ardts, van der Velde, & Maurer, 2010;Bulut & Culha, 2010). We follow in this vein for the present study, particularly as we adopt Mowday and colleagues' (1979) definition of organizational commitment, which has been explicitly identified as having an affective orientation (Meyer & Allen, 1997;Paul & Anantharaman, 2003).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Third, previous research on IRB has reported mixed results for the age–IRB relationship. Whereas some studies report a positive age–IRB relationship (Ardts, van der Velde, & Maurer, ; Choi, ), others report a null relationship (Carmeli, Meitar, & Weisberg, ; Zhou, Zhang, & Montoro‐Sanchez, ) or even a negative relationship (Axtell et al, ; Janssen, ) between the two constructs.…”
mentioning
confidence: 99%
“…From the I-O literature, if the content is not relevant or directly related to the challenges one currently has, then satisfaction and transfer of training will be low (Ardts et al, 2010;Gentry et al, 2014;Scaduto et al, 2008). We may see similar results if we don't account for these conclusions in our work.…”
Section: Training and Developmentmentioning
confidence: 78%